Biochemical properties of mammalian TREX1 and its association with DNA replication and inherited inflammatory disease. (20th May 2009) - Lindahl, Tomas; Barnes, Deborah E.; Yang, Yun-Gui; Robins, Peter
Abstract : The major DNA-specific 3′–5′ exonuclease of mammalian cells is TREX1 (3′ repair exonuclease 1; previously called DNase III). The human enzyme is encoded by a single exon and, like many 3′ exonucleases, exists as a homodimer. TREX1 degrades ssDNA (single-stranded DNA) more efficiently than dsDNA (double-stranded DNA), and its catalytic properties are similar to those of Escherichia coli exonuclease X. However, TREX1 is only found in mammals and has an extended C-terminal domain containing a leucine-rich sequence required for its association with the endoplasmic reticulum. In normal S-phase and also in response to genotoxic stress, TREX1 at least partly redistributes to the cell nucleus. In a collaborative project, we have demonstrated TREX1 enzyme deficiency in Aicardi–Goutières syndrome. Subsequently, we have shown that AGS1 cells exhibit chronic ATM (ataxia telangiectasia mutated)-dependent checkpoint activation, and these TREX1-deficient cells accumulate ssDNA fragments of a distinct size generated during DNA replication. Other groups have shown that the syndromes of familial chilblain lupus as well as systemic lupus erythematosus, and the distinct neurovascular disorder retinal vasculopathy with cerebral leukodystrophy, can be caused by dominant mutations at different sites within the TREX1 gene.